NUTRITIONAL COMPOSITIONS OF SIX EDIBLE INSECTS IN JAVA - Kuntadi, Kuntadi; Adalina, Yelin; Maharani, Kun Esti (Indonesian Journal of Forestry Research, 2018)
Nutritional deficiency is still a problem faced by many families in Indonesia. One of the important issues is the level of protein consumption that is still below the minimum required standard. Edible insects could be one alternative of protein sources since their availability in the nature is quite abundant. This paper analyses six edible species of both cultivated and wild insects for its proximate compositions to measure their nutritional value. The cultivated insects consist of cricket (Gryllus sp.), giant mealworm (Zophobas morio F.), yellow mealworm (Tenebrio molitor L.), and silkworm (Bombyx mori L.), and the wild insects consist of javanese grasshopper (Valanga nigricornis Burm.) and paddy locust (Nomadacris succincta L.). Results shows that the nutritional composition of insects varies widely. Each 100g of dry weight contains of 32.59-76.69% of protein, 6.9-29.47% of fat, 0.92-30.76% of carbohydrate, 2.80-5.79% of ash, 407.34- 517.50 kcal of energy, and minerals about 24.82-31.22 mg of calcium (Ca) and 3.15-4.1 mg of iron (Fe). Some species such as grasshoppers, silkworm pupae and crickets have high protein content which potentially can be utilized as an alternate protein sources to fight against malnutrition and to increase nutritious food consumption. Efforts should be made to encourage the consumption of edible insects as an alternative source of protein. It is especially important to those who live in and around the forest, since the forest area is an excellent habitat for various species of insects.